Investigating multi-generational IS teams collaboration - Machado, Sofia Maria Bouzon; Diirr, Bruna (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: Producing innovative solutions is a challenge for organizations and their Information Systems (IS) teams. Innovation is closely related to collaboration among professionals beyond the scope of specific individual ages, skills, and knowledge. Problem: Collaboration between people with heterogeneous work experiences is widely discussed in the literature in different areas of knowledge but does not highlight Information Systems (IS) team collaboration. Furthermore, there is no clear understanding of the generation and professional background diversity impact on the performance of IS teams. Solution Proposal: This study aims to identify how age and professional experience diversity impact work groups collaboration from the perspective of professionals who belong to IS teams. The proposal is to obtain inputs for these IS teams to improve their performance. IS Theory: The research was developed under the aegis of the Social Exchange Theory, particularly concerning the exchange of non-material goods. Method: A field study was conducted based on structured interviews and qualitative analysis. Results: In general, it was observed performance impact on IS teams. It was also noticed that the impact on the collaboration was perceived in different ways, depending on the generation and professional skill of team members. This study identified the benefits and challenges of having generation diversity on IS teams collaboration. Contributions and Impacts to IS Area: The impacts of generation and professionals’ background diversity on collaboration were identified and can serve as input for planning activities in age-diverse teams in order to enhance benefits and minimize obstacles. Using insights from Social Exchange Theory, the results reinforce that intergenerational collaboration is fundamental in creative processes. Furthermore, the study contributes to the Grand Challenge of Research in Information Systems (IS) in Brazil “Systemic and Socially Conscious Perspective for Information Systems”, for addressing age diversity in IS teams.